Characterization of New Flavored Oils Obtained Through the Co-Milling of Olives and Vegetable Food Products - Celeste Lazzarini; Matilde Tura; Mara Mandrioli; Marco Setti; Noureddine Mokhtari; Abdelaziz Ait Elkassia; Sara Barbieri; Enrico Valli; Alessandra Bendini; Tullia Gallina Toschi (Foods, 2025)
Consumers are increasingly attracted to innovative, gourmand, and sustainable food products. This has led to a growing interest in flavored olive oils through co-milling processing. This study explores the production and characterization of flavored olive oils obtained by co-milling olives with orange pomace, black pepper, and hemp seeds, aiming to enhance their sensory and compositional properties while promoting sustainability through the valorization of agri-food by-products. The flavored olive oils and their control samples were analyzed for free acidity, tocopherols, phenolic compounds, volatiles, and sensory profiles. The flavored oils exhibited an acceptable hydrolytic state and peculiar sensory notes, depending on the ingredients used, as well as enhanced compositional qualities. This research highlights the potential of using oranges and hemp by-products in flavored oil production, offering an innovative approach to reducing food waste, with the possibility of future industrial applications.